Analysis of the effect of the combination of fly ash, plastic waste, and natural stone waste as a substitute additive for making environmentally friendly concrete on the compressive strength of concrete - Maulana, Muhammad Agung; Septian, Fadhlan Ghifari; Ramadon, Deni; Roesdiana, Tira (Indonesian Journal of Multidisciplinary Science, 2025)
The ongoing development of infrastructure technology, particularly in constructing buildings, plays a vital role in national progress. Concrete, a widely used construction material, is crucial for civil works and overall development.In this study using an innovation in concrete mixes by utilizing waste that can damage the environment, such as fly ash as a cement additive, plastic waste as a coarse aggregate additive, natural stone waste as a fine aggregate additive. The primary objectives of this study are to assess the impact of waste addition on concrete production, establish optimal and minimal waste variations affecting concrete compressive strength, and evaluate the performance of waste mixtures in comparison to normal concrete. Various waste percentages were integrated into the concrete mix: fly ash (5%, 10%, 15%, 20%, 25%, 30%), plastic waste (2%), and natural stone waste (40%). Test specimens were cube-shaped, measuring 15x15x15 cm. Concrete curing took place over 7, 14, 21, and 28 days, with subsequent compressive strength testing. . From the analysis results show a significant correlation between the proportion of added ingredients in the concrete mixture tends to increase the compressive strength of concrete at a certain limit, obtained the optimum value at 20% variation with a compressive strength of 328.0036 kg/cm2 and the minimum value at 30% variation with a compressive strength of 276.3318 kg/cm2 at the age of 28 days, the use of waste in concrete mixes is very good and can be an alternative in making concrete with environmentally friendly properties.